Næringargildi geitaafurða – Kjöt og mjólk - Reykdal, Ólafur; Hilmarsson, Óli Þór; Hauksdóttir, Svanhildur (Zenodo, 2019)
This report on the nutrient content of goat meat and goat milk is a part of the project “Added value and special status of goat products”. The project is supported by the Agricultural Productivity Fund and carried out at Matis in cooperation with the Association of Goat Farmers in Iceland. Goat carcasses were cut into legs, loin, forequarters and flanks. Proportions of meat, bones and waste were determined. On the average meat was 66% of the carcasses, bones 31% and waste 3%. The meat was analysed for proximates. The protein content was high (21% protein for meat from the whole carcass). Fat content was generally low (4-24%). Goat milk was sampled from spring until autumn 2018. Each milk sample was collected from composite milk from 3-57 animals. Fat content was on the average 3,9%, protein 3,7% and lactose 3,9%. The contents of polyunsaturated fatty acids and omega-3 fatty acids were higher than in Icelandic cow milk. The results should be valuable for promotion of goat products, work on nutrient declarations and product development. : Funding: Framleiðnisjóður landbúnaðarins